Magnetite Nanoparticles Functionalized with Therapeutic Agents for Enhanced ENT Antimicrobial Properties - Mara Caciandone; Adelina-Gabriela Niculescu; Valentina Grumezescu; Alexandra Cătălina Bîrcă; Ionuț Cosmin Ghica; Bogdan Ștefan Vasile; Ovidiu Oprea; Ionela Cristina Nica; Miruna Silvia Stan; Alina Maria Holban; Alexandru Mihai Grumezescu; Ion Anghel; et al. (MDPI AG, 2022)
In the context of inefficient antibiotics, antibacterial alternatives are urgently needed to stop the increasing resistance rates in pathogens. This study reports the fabrication and characterization of four promising magnetite-based antibiotic delivery systems for ENT (ear, nose and throat) applications. Magnetite nanoparticles were functionalized with streptomycin and neomycin and some were entrapped in polymeric spheres. The obtained nanomaterials are stable, with spherical morphology, their size ranging from ~2.8 to ~4.7 nm for antibiotic-coated magnetite nanoparticles, and from submicron sizes up to several microns for polymer-coated magnetite-antibiotic composites. Cell viability and antimicrobial tests demonstrated their biocompatibility on human diploid cells and their antibacterial effect against Gram-negative (Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) opportunistic bacteria. The presence of the polymeric coat proved an enhancement in biocompatibility and a slight reduction in the antimicrobial efficiency of the spheres. Our results support the idea that functional NPs and polymeric microsystems containing functional NPs could be tailored to achieve more biocompatibility or more antimicrobial effect, depending on the bioactive compounds they incorporate and their intended application.